2021
DOI: 10.1038/s41598-021-01238-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of widowhood and living alone with depression among older adults in India

Abstract: Widowhood is a catastrophic event at any stage of life for the surviving partner particularly in old age, with serious repercussions on their physical, economic, and emotional well-being. This study investigates the association of marital status and living arrangement with depression among older adults. Additionally, the study aims to evaluate the effects of factors such as socio-economic conditions and other health problems contributing to the risk of depression among older adults in India. This study utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 72 publications
3
62
0
2
Order By: Relevance
“…The results revealed that marital status was a significant predictor for major depression among older adults, indicating that currently unmarried older adults who are predominantly those who widowed in the current study have higher levels of depression than married people. This significant association is supported by substantial literature from India as well as other countries [ 26 , 63 , 64 ]. Gahler highlights that marital dissolution is associated with severe social discord and confers an increased risk for psychological distress and overall health deterioration [ 65 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results revealed that marital status was a significant predictor for major depression among older adults, indicating that currently unmarried older adults who are predominantly those who widowed in the current study have higher levels of depression than married people. This significant association is supported by substantial literature from India as well as other countries [ 26 , 63 , 64 ]. Gahler highlights that marital dissolution is associated with severe social discord and confers an increased risk for psychological distress and overall health deterioration [ 65 ].…”
Section: Discussionsupporting
confidence: 62%
“…Also, residing with family is most preferred and satisfactory living arrangement among older people in India which is associated with improved psychological wellbeing [ 23 25 ]. A recent study in India found that older adults who lived alone and were widowed had higher chances of depression [ 26 ]. Similarly, the impaired social relationships are associated with depression, and other mental and physical illnesses [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian context, the majority of studies on health problems and ageing have focussed on the consequences of individual diseases among older adults. For instance, studies by Chauhan et al (2021) and Srivastava et al (2021) have evaluated the repercussions of living arrangements and other behaviour health factors on depression among older adults in India [ 40 , 41 ]. A community level study on primary care population in India estimated high prevalence of multimorbidity among older adults, women and individuals of high socioeconomic status, and significant gender differences in prevalence of multimorbidity have been reported [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caste was coded as Scheduled Tribe, Scheduled Caste, Other Backward Class and others [ 23 ]. Others include those who were identified as having higher social status [ 24 , 25 ]. Place of residence was coded as urban and rural.…”
Section: Methodsmentioning
confidence: 99%